Surgical services initiative: Taking modern surgery to the poor - J Gnanaraj; Sungtiakum Jamir (Wolters Kluwer Medknow Publications, 2014)
Mobile surgical services have the inherent advantage that surgical conditions can be diagnosed and treated in a cost effective way in rural as well as remote areas. The Surgical Services Initiative comprises a group of doctors who have joined hands to help the poor and marginalized sections of the population by making modern surgical treatment available to them. The experience and details of one such surgical camp held over one month is presented in this article. The diagnostic and surgical camp model is also described here.